Una macro estrategia para el desarrollo de la creatividad desde la experimentación. Orientaciones prácticas - Escudero Herrera, Betty (2014)
This article explains the basics for working with creative expression and appreciation with manual activities, the main tool hands. The person that holds manual skills over time have been sleeping for various personal, economic and even social situations; limiting their creativity. Finally, the macro strategy is explained as a contribution on the creation, transformation and innovation from direct or an experience taught during growth is stimulated.